Определение погонных электротехнических параметров нефтепогружного кабеля - Глазырин А. С. Александр Савельевич; Исаев Ю. Н. Юсуп Ниязбекович; Кладиев С. Н. Сергей Николаевич; Леонов А. П. Андрей Петрович; Раков И. В. Иван Витальевич; Колесников С. В. Станислав Вячеславович; Ланграф С. В. Сергей Владимирович; Филипас А. А. Александр Александрович; Копырин В. А. Владимир Анатольевич; Хамитов Р. Н. Рустам Нуриманович; Ковалев В. З. Владимир Захарович; Лавринович А. В. Алексей Валериевич (2021, 2021)
Заглавие с титульного листа